Cigarette smoking and gastric cancer in the Stomach Cancer Pooling (StoP) Project. Issue 2 (March 2018) - Praud, Delphine; Rota, Matteo; Pelucchi, Claudio; Bertuccio, Paola; Rosso, Tiziana; Galeone, Carlotta; Zhang, Zuo-Feng; Matsuo, Keitaro; Ito, Hidemi; Hu, Jinfu; Johnson, Kenneth C.; Yu, Guo-Pei; et al.
Abstract : Tobacco smoking is a known cause of gastric cancer, but several aspects of the association remain imprecisely quantified. We examined the relation between cigarette smoking and the risk of gastric cancer using a uniquely large dataset of 23 epidemiological studies within the 'Stomach cancer Pooling (StoP) Project', including 10 290 cases and 26 145 controls. We estimated summary odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) by pooling study-specific ORs using random-effects models. Compared with never smokers, the ORs were 1.20 (95% CI: 1.09–1.32) for ever, 1.12 (95% CI: 0.99–1.27) for former, and 1.25 (95% CI: 1.11–1.40) for current cigarette smokers. Among current smokers, the risk increased with number of cigarettes per day to reach an OR of 1.32 (95% CI: 1.10–1.58) for smokers of more than 20 cigarettes per day. The risk increased with duration of smoking, to reach an OR of 1.33 (95% CI: 1.14–1.54) for more than 40 years of smoking and decreased with increasing time since stopping cigarette smoking ( P for trend<0.01) and became similar to that of never smokers 10 years after stopping. Risks were somewhat higher for cardia than noncardia gastric cancer. Risks were similar when considering only studies with information on Helicobacter pylori infection and comparing all cases to H. pylori + controls only. This study provides the most precise estimate of the detrimental effect of cigarette smoking on the risk of gastric cancer on the basis of individual data, including the relationship with dose and duration, and the decrease in risk following stopping smoking. Abstract : Supplemental Digital Content is available in the text.